2007
DOI: 10.5688/aj7106120
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Approaches to Learning in an Australian University

Abstract: Objectives. To investigate how pharmacy students' approaches to learning change over the duration of a bachelor of pharmacy degree program. Methods. Data were obtained from a cross-sectional, repeated measures design, using a validated self-report survey instrument. Areas examined included processing and regulation strategies, motivational preferences for learning, and the relationship between approaches to learning and academic performance.Results. Pharmacy students were strongly vocationally oriented in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…Vermunt (2005) explained these disciplinary differences in the learning patterns students adopt by a combination of differences in the nature of the discipline, differences in dominant pedagogical practices in the different disciplines, and differences between the students who choose to study particular disciplines. Smith et al (2007) found a strong dominance of application-directed learning among Pharmacy students in Australia for all year groups, a dominance that stayed stable throughout the study. This finding shows similarities with results from Lindblom-Ylänne and Lonka (2000), who found a clear and separate application-directed learning factor among advanced and adult medical students.…”
Section: Relations Of Learning Patterns With Contextual Factorsmentioning
confidence: 96%
See 3 more Smart Citations
“…Vermunt (2005) explained these disciplinary differences in the learning patterns students adopt by a combination of differences in the nature of the discipline, differences in dominant pedagogical practices in the different disciplines, and differences between the students who choose to study particular disciplines. Smith et al (2007) found a strong dominance of application-directed learning among Pharmacy students in Australia for all year groups, a dominance that stayed stable throughout the study. This finding shows similarities with results from Lindblom-Ylänne and Lonka (2000), who found a clear and separate application-directed learning factor among advanced and adult medical students.…”
Section: Relations Of Learning Patterns With Contextual Factorsmentioning
confidence: 96%
“…One of these was the already mentioned application-directed learning pattern, which was found mainly among adult students in the Dutch sample. However, clear application-directed learning dimensions have also been reported by Smith et al (2007) among Pharmacy students at an Australian university and by Lindblom-Ylänne and Lonka (2000) among advanced medical students in Finland. Another pattern that showed up in many but not all samples was one combining all conceptions of learning, with almost no loadings from other scales.…”
Section: Learning Patterns In New International Contexts and Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 An earlier study showed that pharmacy students who are self-reflective in their learning environments and have skills in collaborative learning are best equipped to construct and apply knowledge, rather than simply to accumulate and reproduce it. 11,12 We sought to address the lack of relevant patient self-management curriculum content, multimediafocused students, and the need to ensure knowledge acquisition and construction by developing a patient-focused learning module incorporating online lectures and readings, video-recorded interviews of patient accounts, and classroom-based discussions.…”
Section: Introductionmentioning
confidence: 99%